[SPS seminar on identity - 18 June 2011] - A digression on identity. - Carli, Renzo (Rivista di Psicologia Clinica, 2011)
A differentiation is made between emotional identity, based on polysemic thought, and identity organised by the principle of identity and by that of non-contradiction. Here identity consists of recognising that “I am I” and “I am not the other person”. The differentiation is then suggested between knowledge, typical of the unconscious mode of being, and recognition, which organises identity and the relation with the other person: recognising and being recognised.